Confronting segregation of care in OBGYN: a national survey of program directors - Karampreet Kaur; Annie Apple; Rebecca Hamm; Allison Schachter; Catherine Salva; Sarita Sonalkar; Kavita Vinekar; Shyann Hall; Abike James; Arina Chesnokova (Journal of Health Equity)
Background The structure of ambulatory care in teaching hospitals may contribute to disparities in reproductive outcomes, particularly when outpatient care is segregated by insurance status and race.Objective To investigate the prevalence and characteristics of separate faculty and resident practices in obstetrics and gynecology (OBGYN), including payor and racial segregation.Methods Electronic survey administered to OBGYN Residency Program Directors (PDs) from March to September 2023.Results Ninety-two of 299 PDs responded (31%). Sixty-one programs (66%) reported separate resident and attending practices. Patient assignment was based on appointment availability (77%), patient request (54%), and insurance (37%). Only 30% of programs with separate practices collected data comparing patient demographics, care quality, or outcomes between practices; among these, 72% reported at least one demographic disparity, including differences in race (28%), insurance (67%), and socioeconomic status (61%). A majority reported similar quality of care and patient outcomes between practices, and 64% reported no efforts to integrate.Conclusions Separate attending and resident ambulatory practices in OBGYN are prevalent and can result in segregated care. National guidance is needed to promote equitable outpatient care while ensuring strong educational experiences. Solutions must be data-driven, locally-tailored, and developed in collaboration with patients, clinicians, educators, and professional organizations.